Malaysian Dietary Guidelines for Children and Adolescents 2023 - Mat Jusoh, Hanapi; Abd Talib, Ruzita; Aris, Norliyana; Buhari, Siti Sabariah; Anwar, Nurul Hayati; Shaari, Nur Dayana; Sakiram, Norwati (National Coordinating Committee on Food and Nutrition (NCCFN), Ministry of Health Malaysia, 2023)
The documentation of the Malaysian Dietary Guidelines (MDG) for Children and Adolescents 2023 was coordinated by the Technical Working Group (TWG) on Nutritional Guidelines, which is under the purview of the National Coordinating Committee on Food and Nutrition (NCCFN), Ministry of Health Malaysia. The Nutrition Division, Ministry of Health Malaysia served as the secretariat for the Malaysian Dietary Guidelines for Children and Adolescents.